Metode QFD dan TRIZ dalam Perancangan Kontainer Berpendingin pada Sepeda Motor sebagai sarana Penjualan dan Pengantaran Sayuran - Ratna Sari Dewi; Ahmad Rusdiansyah; Farhan Herdiansyah (invotek, 2020)
The freshness of vegetables cannot always be sustained because vegetables are one of the perishable horticultural products. The decline of freshness of these vegetables is due to physical, chemical, and physiological factors which appear naturally after the harvesting process. To ensure the freshness of vegetables when distributed, refrigerated containers were designed in this study by combining the Quality Function Deployment (QFD) and Teoriya Reshenia Izobretatelskikh Zadatch (TRIZ). To get the voice of customer as the main input in the QFD method, interviews were conducted to 10 vegetable producers in Indonesia as potential consumers of designed refrigerated container products. Contradictions that arise between several technical responses in QFD are resolved by the TRIZ method. As the final result, this study recommends 12 target specifications that can be implemented on the prototype of the designed refrigerated container.